Evaluation of combined heat and mass transfer in hydromagnetic micropolar flow along a stretching sheet when viscous dissipation and chemical reaction is present - B. Saidulu; K. Sreeram Reddy (Partial Differential Equations in Applied Mathematics, 2023)
In this study, the problem of heat and mass transfer in the hydromagnetic flow of a micropolar fluid through a stretching sheet with an existence of viscous dissipation and chemical reaction. By using MATLAB inbuilt bvp4c approach, we are able to numerically solve the converted equations for the flow regime. The influence of key factors on the velocities, microrotations, temperatures, and concentration functions has been analyzed. The magnetic field has been measured and found to The micropolar factor has the reverse impact on all functions excluding temperature, whereas the microrotational parameter slows things down and raises temperature and concentration function. When the Eckert number increases, the temperature rises and the concentration falls with enhanced values of Schmidt number.